IMPROVEMENT OF LIBRARY AND LIBRARY MAINTENANCE IN THE LIBRARY OF THE UNIVERSITY (Pedagogy of Higher and Secondary Education, 2008)
Modern forms and methods of library-bibliographic service in the university library are being considered, the impontance of computerizing of libraries is stressed.